Application of biogenically- synthesized silver nanoparticles to groundwater treatment - Otoo, Dennis Kweku (University of Cape Coast, 2024)
The proliferation of landfill sites has necessitated the need for effective remediation techniques to mitigate potential deterioration of groundwater quality. This study presents a novel approach to groundwater treatment near landfill sites through the synthesis of silver nanoparticles (AgNPs) using biogenic materials-specifically tiger nut, papaya peel, and noni leaves. These locally-sourced materials offer a cost-effective and sustainable means to catalyze the synthesis process, while also capitalizing on their essential properties that contribute to the reduction of silver ions. Characterization of the synthesized nanoparticles was performed using UV-visible spectroscopy, Fourier transform infrared spectroscopy and scanning electron microscopy (SEM), confirming the formation of spherical nanoparticles with an average size of 10-50 nm. AgNPs optimized for maximal adsorption and reactive capability, and the application was targeted to sites with significant heavy metal and microbial contamination as indicated by initial site surveys. The efficiency of the nanoparticles as contaminant removal media was tested in situ with water samples obtained from multiple points around the landfill sites. Parameters such as pH, heavy metal concentration, and microbial load were monitored before and after treatment. Results proved a significant reduction in heavy metals, with over 90% removal efficiency for Cr (IV), Co (II), Mn (II) and Fe (II). Moreover, bactericidal efficacy was confirmed with a differential reduction in total coliform counts. The use of these bio-sourced materials not only enhanced the synthesis process but also introduced additional phytochemicals that aided in the overall treatment efficacy.
xvii, 165p;, ill
Keywords: Biogenic Synthesis; Groundwater Pollution; Heavy Metal; Landfill Site; Microbial Contamination; Silver Nanoparticle